1998
DOI: 10.1016/s1074-7613(00)80671-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Th1 Development Mediated by GATA-3 through an IL-4-Independent Mechanism

Abstract: Recently, the transcription factor GATA-3 was shown to be selectively expressed in Th2 but not Th1 cells and to augment Th2-specific cytokines. Here, we show that loss of GATA-3 expression by developing Th1 cells requires IL-12 signaling through Stat4 and does not simply result from an absence of IL-4. Moreover, we demonstrate a novel role for GATA-3 in directly repressing Th1 development distinct from its positive actions on Th2-specific cytokines. GATA-3 inhibits Th1 cytokines by a cell-intrinsic mechanism t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
642
5
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 714 publications
(690 citation statements)
references
References 56 publications
38
642
5
5
Order By: Relevance
“…It has been suggested that cytokines and their receptors, transcription factors, MHC determinants, Ag peptides, and costimulatory signals are important for Th1 and Th2 cell differentiation 1 2 3 4 5 6 7 8 9. However, to date, the precise mechanism responsible for the differentiation and development of polarized Th1 responses has not been fully clarified in humans.…”
mentioning
confidence: 99%
“…It has been suggested that cytokines and their receptors, transcription factors, MHC determinants, Ag peptides, and costimulatory signals are important for Th1 and Th2 cell differentiation 1 2 3 4 5 6 7 8 9. However, to date, the precise mechanism responsible for the differentiation and development of polarized Th1 responses has not been fully clarified in humans.…”
mentioning
confidence: 99%
“…The MSCV-based bi-cistronic retroviral vector is a commonly used system for ectopic expression of cDNA [33][34][35][36], in which surface expression of the marker protein not only correlates with the successful expression of the gene of interest [37], but also enables to identify and isolate individual, successfully transduced T lymphocytes according to the expression of human CD4 (hCD4) (Fig. 1A, right).…”
Section: Generation and Retroviral Expression Of Shp-2 Isoforms In Prmentioning
confidence: 99%
“…The expression of these transcription factors is induced as Th precursor cells become Th2 e ectors. Interestingly, the induction of GATA-3 expression in Th2 cells has been shown to be dependent on IL-4 stimulated Stat6 activation, although it is unclear whether or not Stat6 activates GATA-3 transcription directly (Ouyang et al, 1998). Ectopic expression of activated Stat6 in Th1 cells can also result in the expression of GATA-3 and c-maf in these cells (Kurata et al, 1999).…”
Section: Stat6 and T Helper Cell Differentiationmentioning
confidence: 99%